The Issue of Human Rights Violation Towards Rohingnya Ethnic Group and the Role of International Community - Ardli Johan Kusuma (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
This writing discusses the issue of human rights violation towards Rohingnya ethnic group in Myanmar, as well as the efforts made by international community to fight for Rohingnya’s right to be free from Human Rights violation. This writing is decsriptive and analitical by using qualitative method, the data collecting technic is “library research” where the data used to support the argument are obtained by collecting them from various sources such as books or literature, journal, newspaper, magazine, as well as data taken from the internet. The result of the discussion from this writing indicates the existence of the fact that human rights violation towards Rohingnya ethnic group occured in Myanmar as referred to International Human Rights Norm in United Nations Instrument (A universal declaration on Human Rights in 1948). In addition to that, international community is not yet able to persuade Myanmar Government to stop the human rights violation that occurs. International community with modern international network (Transnational Advocacy Networks) should be able to persuade Myanmar to respect human rights especially in the case of Rohingnya ethnic group so that this case ends.   Keywords: International Human Rights Norm, Rohingnya Ethnic Group, Universal Declaration of  Human Rights, Transnational Advocacy Networks.